'-Tul' in Korean both as an Associative and as an Additive Plural Marker - 박명관 (Journal of cognitive science, 2023)
This paper investigates the grammatical identity of the plural marker ‘-tul’ in Korean. We first explore this issue from comparative morpho-syntactic perspectives. Noting that like in Turkish but unlike in English, ‘-tul’ can give rise to associative plurality, we propose that as cross-linguistically attested, it is generated in the outer layer of a nominal projection. Showing that ‘-tul’ with a common noun allows for an additive plural (ADP) (or sum) reading as well as an associative plural (ASP) (or ADP-like) one, we argue that the attempt to deduce the former reading from the latter one does not work out. Particularly, ‘-tul’ with some collective nouns in Korean yields a genuine kind of additive plurality. Thus, it is safe to say that ‘-tul’ in Korean serves both as an ASP and as an ADP marker, which the ASP-only approach by Jiang (2017) and Nakanish (2018) cannot capture. To further support this thesis, we move on to examine the plural markers in East Asian languages to show that Korean ‘-tul’ behave syntactically like Japanese ‘-tachi’ but unlike Chinese ‘-men.’ KCI Citation Count: 0